2021
DOI: 10.1136/bmjoq-2020-001266
|View full text |Cite
|
Sign up to set email alerts
|

Approaches, enablers, barriers and outcomes of implementing facility-based stillbirth and neonatal death audit in LMICs: a systematic review

Abstract: PurposeTo identify approaches, enablers, barriers and outcomes of facility stillbirth and neonatal death audit in low-income and middle-income countries (LMICs).Data sourcesWe searched MEDLINE, CINAHL Complete, Academic Search Index, Science Citation Index, Complementary index and Global health electronic databases.Study selectionStudies were considered eligible when reporting the approaches, enablers, barriers and outcomes of facility-based stillbirth and neonatal death audit in LMICs.Data extractionTwo autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Our finding regarding nursery ward space is inconsistent with the WHO 2020 standards for providing high-quality care to small and sick newborns [20]. Limited nursery beds resulted in nursing more than one baby in a single cot increasing the risk of infection and overburdening staff [24][25][26][27]. Hospital-acquired infections among neonates cause about 30-40% of neonatal deaths [28].…”
Section: Infrastructurementioning
confidence: 73%
“…Our finding regarding nursery ward space is inconsistent with the WHO 2020 standards for providing high-quality care to small and sick newborns [20]. Limited nursery beds resulted in nursing more than one baby in a single cot increasing the risk of infection and overburdening staff [24][25][26][27]. Hospital-acquired infections among neonates cause about 30-40% of neonatal deaths [28].…”
Section: Infrastructurementioning
confidence: 73%
“…Fear and distrust amongst health workers, characteristic of this culture, act to supress openness, practice learning and innovation and result in increasing errors and poor-quality health care [29] . For example, the existence of blame culture has recently been acknowledged as a barrier to perinatal death reviews, advanced as an important strategy to reduce stillbirth in sub-Saharan Africa settings [30] . In HIC settings, organisations are increasingly encouraged to move away from a focus on blaming individuals, towards acknowledging systems factors, alongside individual responsibility, and learning [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Data from Sierra Leone reported that stakeholders' involvement allows a direct confrontation with the reaching of targets, increases the readiness to support the implementation of MDSR activities in the community and it helps the user of the services to provide new ideas and inputs that could improve the process. 21 Moreover, the study conducted by Adrian et al ( 2016) in Sub-Saharan Africa also reported that the involvement of individuals in the implementation process promotes individual accountability towards implementing the intervention 22 . Other studies emphasized the role of multilevel involvement of stakeholders in the prompt correction of mistakes, wherever a supportive supervision is put in place.…”
Section: Discussionmentioning
confidence: 99%
“…20 The inclusion of different professional figures in the team has been considered as a positive element of the implementation process in previous studies. 22 Multidisciplinary teams should include various cadres not only at the facility level, but also external stakeholders from ministries of health and other implementing partners at subnational and national levels. 20 Because of cultural differences usually present within an organization across ranks, occupation, clinical specialties and operating units, 19 in an environment favouring inclusion and confrontation a multidisciplinary team can act as a catalyzer for collective learning.…”
Section: Discussionmentioning
confidence: 99%